Actividades de Control de las Cuentas Por Pagar en La Industrial Fideera Rodolfo Pazmiño - Reasco Gavilanes, Sally Celeste (2019)
The present case study work entitled "Control activities of accounts payable by Industrial Fideera Rodolfo Pazmiño of the City of Babahoyo", focuses on the analysis of accounts payable to suppliers, with the purpose of maintaining a liquidity that Cover these debts in the short term. One of the main accounts held by an operating company are the accounts payable, since they are the ones that control each of the debts that the entity has with third parties, the same ones that provide products and services that help cover the needs of the Consumers of the plant in their industrial processes.